2022
DOI: 10.1111/liv.15473
|View full text |Cite
|
Sign up to set email alerts
|

Relative adrenal insufficiency in the non‐critically ill patient with cirrhosis: A systematic review and meta‐analysis

Abstract: Background & Aims Characterization of relative adrenal insufficiency (RAI) in cirrhosis is heterogeneous with regard to studied patient populations and diagnostic methodology. We aimed to describe the prevalence and prognostic importance of RAI in non‐critically ill patients with cirrhosis. Methods A systematic review and meta‐analysis was performed using MeSH terms and Boolean operators to search five large databases (Ovid‐MEDLINE, ScienceDirect, Web of Science, Cochrane Library and http://clinicaltrials.gov)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Interestingly, prior literature has shown that TC levels correlate well with both plasma free cortisol and salivary cortisol levels in patients with cirrhosis, even in patients with moderate to severe hypoalbuminemia. 3,4 Coupled with our finding that subnormal Cosyntropin stimulation responses are associated with a nearly three-fold increased risk of 90-day mortality, 1 early identification of RAI in cirrhosis appears to be more clinically relevant than precise bioactive cortisol measurement.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Interestingly, prior literature has shown that TC levels correlate well with both plasma free cortisol and salivary cortisol levels in patients with cirrhosis, even in patients with moderate to severe hypoalbuminemia. 3,4 Coupled with our finding that subnormal Cosyntropin stimulation responses are associated with a nearly three-fold increased risk of 90-day mortality, 1 early identification of RAI in cirrhosis appears to be more clinically relevant than precise bioactive cortisol measurement.…”
mentioning
confidence: 70%
“…lighted by variance in prevalence estimates depending on methodology, exposition of which was a primary aim of our manuscript. 1 However, binding-globulin independent cortisol forms (i.e., salivary or plasma free cortisol), are not routinely available to clinicians and thus provide lower practical utility. Interestingly, prior literature has shown that TC levels correlate well with both plasma free cortisol and salivary cortisol levels in patients with cirrhosis, even in patients with moderate to severe hypoalbuminemia.…”
mentioning
confidence: 99%
“…We have read with interest the review by BJ Wentworth et al, 1 which assessed cortisol in 22 studies of patients with stable cirrhosis, mostly by standard dose cosyntropin stimulation tests. They reported a high incidence of reduced peak or delta cortisol postcosyntropin, 29% and 36% respectively.…”
Section: Plasma Corticosteroid-binding Globulin Concentrations Are Pr...mentioning
confidence: 99%
“…The prevalence of relative adrenal insufficiency positively correlated with disease severity defined by Childs Pugh score. 1 Corticosteroid-binding globulin (CBG) was not measured.…”
Section: Plasma Corticosteroid-binding Globulin Concentrations Are Pr...mentioning
confidence: 99%
“…Adrenal dysfunction (AD) is common in cirrhosis but infrequently diagnosed in clinical practice [1]. Its prevalence correlates with the severity of underlying liver disease and carries prognostic implications [2,3]. Multiple studies demonstrate that an abnormal cortisol stimulation response is associated with an increased risk of short-to-medium-term mortality, independent of the underlying liver disease [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%